2015
DOI: 10.1104/pp.15.00851
|View full text |Cite
|
Sign up to set email alerts
|

MUCILAGE-RELATED10 Produces Galactoglucomannan That Maintains Pectin and Cellulose Architecture in Arabidopsis Seed Mucilage

Abstract: Plants invest a lot of their resources into the production of an extracellular matrix built of polysaccharides. While the composition of the cell wall is relatively well characterized, the functions of the individual polymers and the enzymes that catalyze their biosynthesis remain poorly understood. We exploited the Arabidopsis (Arabidopsis thaliana) seed coat epidermis (SCE) to study cell wall synthesis. SCE cells produce mucilage, a specialized secondary wall that is rich in pectin, at a precise stage of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
229
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(239 citation statements)
references
References 103 publications
9
229
1
Order By: Relevance
“…Despite their low abundance, these components could play essential roles in controlling mucilage properties (Voiniciuc et al, 2015c). For example, glucomannans and galactoglucomannans synthesized by CSLA2 and MUCI10 seem to be involved in structuring the adherent layer of mucilage (Yu et al, 2014;Voiniciuc et al, 2015b). Determining how these different polymers are involved in RG-I attachment to cellulose is challenging, and it is unclear which are part of the mucilage itself or originate from fragments of primary cell wall released when the epidermal cells rupture on imbibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their low abundance, these components could play essential roles in controlling mucilage properties (Voiniciuc et al, 2015c). For example, glucomannans and galactoglucomannans synthesized by CSLA2 and MUCI10 seem to be involved in structuring the adherent layer of mucilage (Yu et al, 2014;Voiniciuc et al, 2015b). Determining how these different polymers are involved in RG-I attachment to cellulose is challenging, and it is unclear which are part of the mucilage itself or originate from fragments of primary cell wall released when the epidermal cells rupture on imbibition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to Xyl branching of RG-I, other pectin modifications also would appear to influence adherence, and these remain to be characterized. Glucomannans and galactoglucomannans can interact with cellulose and appear to participate in the organization and crystallization of mucilage cellulose (Yu et al, 2014;Voiniciuc et al, 2015b). csla2 and muci10 mutants affected in glucomannan and galactoglucomannan synthesis have more densely packed adherent layer polymers, with a small repartitioning of RG-I to the outer mucilage layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of mannan have yet to be explored in great detail, although new insights into their structural roles were gained in recent years (Yu et al, 2014;Voiniciuc et al, 2015a). Some mAb probes are available (e.g.…”
Section: Xylan Dynamics In Secondary Cell Wallsmentioning
confidence: 99%
“…Recently, heteromannan produced by CELLULOSE SYNTHASE-LIKE A2 (Yu et al, 2014) and MUCILAGE-RELATED10 (MUCI10; Voiniciuc et al, 2015a) was shown to control the density of polysaccharides in the mucilage capsule. Using a coexpression and sequencebased strategy, we predicted that MUCI10 (GT34 member) is a mucilage biosynthetic gene.…”
mentioning
confidence: 99%